Preparation method of porous crystalline-amorphous Ge coexisting composite anode material
The porous crystal-amorphous Ge coexisting composite anode material was prepared by hydrothermal method and high-temperature and high-pressure reaction purification, which solved the problem of volume expansion of germanium anode material resulting in capacity decay during charge and discharge, and achieved the effect of improving the specific capacity and cycle stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411766553.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The huge volume expansion caused by Li+ embedded/de-embedded commercial germanium anode materials during charging and discharging leads to rapid capacity attenuation.
Amorphous GeO2/C was prepared by hydrothermal method, and after annealing in air atmosphere and sintering in reducing atmosphere, crystal and amorphous Ge powder were obtained. Then, the porous Ge precursor powder was purified in high temperature and high pressure reaction to obtain porous crystalline-amorphous Ge coexistence composite anode material.
This material can buffer volume changes during charging and discharging, increase the adsorption active site of lithium ions, reduce the transmission distance of lithium ions, accelerate ion diffusion, and improve the specific capacity and long-term cycle stability of lithium ion batteries.
Smart Images

Figure HDA0005169100030000011 
Figure HDA0005169100030000012 
Figure HDA0005169100030000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, belonging to the technical field of alloyed anode materials for lithium ion batteries. Background Art
[0002] Currently, the commercial negative electrode materials for lithium-ion batteries are mainly graphite and lithium titanate. The theoretical capacities of graphite and lithium titanate are 372mAh / g and 175mAh / g, respectively. The energy density and theoretical capacity of graphite and lithium titanate are very limited, which results in the battery's cycle capacity being limited and unable to meet the needs of current high-power equipment.
[0003] However, the traditional alloy preparation method requires the use of a high temperature environment to melt the two metals of copper and gallium separately, and then mix them evenly to make an alloy. This method requires a high temperature environment, complex system equipment, cumbersome and time-consuming production methods, usually going through multiple steps, and high cost and low convenience, so the application of this method is greatly limited. In particular, directly mixing copper powder with liquid metal not only has a poor fusion effect, but also causes a large amount of oxidation of the liquid metal, greatly affecting the effect of forming the alloy.
[0004] Anode materials act as Li in lithium-ion batteries + The receiving device is one of the indispensable core components of lithium-ion batteries. The development of high energy density and high stability negative electrode materials and the reasonable design of the structure can significantly improve the volume energy density and long-term cycle stability of the battery during the charge and discharge cycle. With the rapid development of society, the development of new negative electrode materials with high energy density has become one of the key research objects of scientists. The theoretical capacities of the current main commercial negative electrode materials, graphite and lithium titanate, are 372mAh / g and 175mAh / g, respectively, and there is almost no room for improvement. Therefore, the development of the next generation of new high-capacity negative electrode materials plays an important role in the rapidly developing society. Summary of the invention
[0005] In view of the fact that commercial germanium negative electrode materials in the prior art are converted from Li + The huge volume expansion during embedding / de-embedding leads to rapid capacity decay.
[0006] The present invention uses germanium dioxide as a germanium source, and prepares a reaction product amorphous GeO2 / C by a hydrothermal method, and obtains crystalline and amorphous Ge powders after air atmosphere annealing and reducing atmosphere sintering, and then obtains a porous Ge precursor powder by high temperature and high pressure reaction purification, and the porous Ge precursor powder is sintered in a protective atmosphere to obtain a porous crystalline-amorphous Ge coexistence composite anode material. The porous crystalline-amorphous Ge coexistence composite anode material is used as a lithium ion battery anode, which can buffer the volume change during the charge and discharge process, increase the adsorption active sites of lithium ions, reduce the transmission distance of lithium ions and accelerate the kinetic process of ion diffusion, thereby improving the specific capacity and long-term cycle stability of the lithium ion battery.
[0007] A method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, the specific steps are as follows:
[0008] (1) dispersing germanium dioxide in deionized water by ultrasonic means to obtain a suspension A, and adding ammonia water dropwise under stirring to completely dissolve the powder in the suspension A into a transparent and clear solution B; the germanium in the solution B exists in the form of NH4H(HGeO3)2;
[0009] (2) at a temperature of 25 to 50° C., dropwise add the hydroxyethylenediamine solution into deionized water, then add lithium difluorooxalate borate powder to obtain solution C, and slowly add solution B into solution C to obtain a mixed solution D;
[0010] (3) The mixed solution D is placed at a temperature of 160-210° C. for reaction for 12-36 hours, cooled to room temperature, separated into solid and liquid, and the solid is washed with deionized water and anhydrous ethanol in turn, and dried to obtain a reaction product E (amorphous GeO2 / C);
[0011] (4) The reaction product E is placed in an air atmosphere for low temperature annealing for 3 to 5 hours, cooled naturally to room temperature, and then placed in a reducing gas for reduction sintering, and cooled to room temperature in the furnace to obtain a pretreated powder F (amorphous / crystalline Ge);
[0012] (5) Ultrasonic dispersion of the pretreated powder F into the mixed solution to obtain solution G, transfer solution G to a high temperature and high pressure hydrothermal reactor, react at a temperature of 150 to 200° C. for 10 to 30 hours, cool to room temperature, separate the solid from the liquid, wash the solid with deionized water and anhydrous ethanol in turn, and dry to obtain a precursor powder (porous Ge); the mixed solution is a mixture of ethylene glycol, deionized water and hydrofluoric acid;
[0013] (6) The precursor powder is sintered under a protective gas and then cooled to room temperature in the furnace to obtain a porous crystalline-amorphous Ge coexisting composite anode material.
[0014] Preferably, the mass concentration of germanium dioxide in the suspension A in step (1) is 5-15%, and the mass concentration of ammonia water is 1-3%.
[0015] Preferably, the mass concentration of the hydroxyethylenediamine solution in solution C of step (2) is 1-10%, and the mass concentration of lithium difluorooxalatoborate is 0.2-2%.
[0016] Preferably, the volume ratio of solution B to solution C in step (2) is 3 to 10:1.
[0017] Preferably, the low-temperature annealing temperature in step (4) is 350-500° C.; the reduction sintering temperature is 500-700° C., and the time is 0.2-3 h.
[0018] Preferably, the reducing gas in step (4) is a hydrogen-argon mixed gas or a hydrogen-nitrogen mixed gas, and the volume content of hydrogen in the reducing gas is 5-15%.
[0019] Preferably, the volume ratio of ethylene glycol to deionized water in the mixed solution of step (5) is 1:1, and the mass concentration of hydrofluoric acid is 0.05-0.2%.
[0020] Preferably, the mass concentration of the pretreated powder F in the solution G in step (5) is 0.5-2.0%.
[0021] Preferably, the protective gas in step (6) is argon or nitrogen, the sintering temperature is 400-700° C., and the sintering time is 1-4 hours.
[0022] The beneficial effects of the present invention are:
[0023] (1) The present invention uses commercial germanium dioxide as a germanium source, uses ammonia water to adjust the pH value of suspension A to dissolve germanium dioxide, uses hydroxyethylenediamine and lithium difluorooxalate borate as additives, uses secondary solvent heat to evenly disperse the germanium source and grow it into a porous crystalline-amorphous Ge coexisting composite anode material under high temperature and high pressure. The preparation conditions are simple, the process route is simple and has low pollution, the price cost is low and the reproducibility is good, and the performance of the negative electrode of a lithium ion battery is excellent;
[0024] (2) The porous crystalline-amorphous Ge coexisting composite anode material of the present invention has a unique nanopore structure, and the crystalline and amorphous coexist. The design of the nanopores can effectively promote the wetting of the electrolyte to the electrode, ensuring sufficient contact between the electrolyte and the active material, and at the same time can also increase its comparative area, reduce and increase the adsorption active sites of lithium ions, and reduce the transmission distance of lithium ions and accelerate the kinetic process of ion diffusion;
[0025] (3) The porous crystalline-amorphous Ge coexisting composite anode material of the present invention can reduce the volume change caused during the charge and discharge process, maintain the integrity of the electrode material structure, increase the active sites for lithium ion reaction, and thus improve the cycle stability and rate performance of the electrode;
[0026] (4) The porous crystalline-amorphous Ge coexisting composite anode material of the present invention retains a micron-sized bulk, which can overcome the problem of high surface activity and easy agglomeration of nanoelectrodes. At the same time, the nanopores provide storage sites for lithium ions, providing a basic guarantee for the excellent electrochemical performance of lithium-ion batteries;
[0027] (5) The reversible specific capacity of the porous crystalline-amorphous Ge coexisting composite anode material of the present invention is 1198 mAh / g after 200 charge and discharge cycles at a current density of 200 mA / g, showing excellent specific capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD diagram of the porous crystalline-amorphous Ge coexisting composite anode material of Example 1;
[0029] Figure 2 The transmission electron microscope, EDS element mapping distribution and selected area electron diffraction SEAD spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of Example 1;
[0030] Figure 3 This is the XRD diagram of the porous crystalline-amorphous Ge coexisting composite anode material of Example 2;
[0031] Figure 4 This is a scanning electron microscope spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of Example 2;
[0032] Figure 5 This is a cycle performance diagram of the lithium ion half-cell of Example 2 after 200 constant current charge and discharge cycles;
[0033] Figure 6 This is the XRD diagram of the porous crystalline-amorphous Ge coexisting composite anode material of Example 3;
[0034] Figure 7 This is a cycle performance diagram of the lithium ion half-cell of Example 3 after 200 constant current charge and discharge cycles. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0036] Example 1: A method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, the specific steps are as follows:
[0037] (1) 0.5 g of germanium dioxide is ultrasonically dispersed in 100 mL of deionized water to obtain a suspension A, and 0.2 mL of 20 wt.% ammonia water is added dropwise under stirring to completely dissolve the powder in the suspension A into a transparent and clear solution B; the germanium in the solution B exists in the form of NH4H(HGeO3)2;
[0038] (2) at a temperature of 25° C., 1 mL of a 1% hydroxyethylenediamine solution was dropwise added into 50 mL of deionized water, and then 0.05 g of lithium difluorooxalate borate powder was added to obtain a solution C, and solution B was slowly added to solution C to obtain a mixed solution D;
[0039] (3) The mixed solution D was placed at a temperature of 160° C. for 12 h, cooled to room temperature, and separated into a solid and liquid state. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain a reaction product E (amorphous GeO2 / C);
[0040] (4) The reaction product E was placed in an air atmosphere, annealed at 350°C for 3 h, cooled naturally to room temperature, and then placed in a reducing gas (H2-Ar mixed gas) for reduction sintering at 500°C for 0.2 h, and cooled to room temperature with the furnace to obtain a pretreated powder F (amorphous / crystalline Ge); the volume fraction of H2 in the H2-Ar mixed gas was 5%;
[0041] (5) 0.5 g of pretreated powder F was ultrasonically dispersed into 80 mL of a mixed solution to obtain a solution G, and the solution G was transferred to a high-temperature and high-pressure hydrothermal reactor, reacted at a temperature of 150° C. for 10 h, cooled to room temperature, and separated from the solid and liquid. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain a precursor powder (porous Ge); the mixed solution was a mixed solution of ethylene glycol, deionized water and hydrofluoric acid, the volume ratio of ethylene glycol to deionized water was 1:1, and the mass concentration of hydrofluoric acid in the mixed solution was 0.05%;
[0042] (6) The precursor powder is placed under protective gas (N2), sintered at 400°C for 1 hour, and then cooled to room temperature to obtain a porous crystalline-amorphous Ge coexisting composite anode material;
[0043] The X-ray diffraction (XRD) spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is shown in Figure 1 ,Depend on Figure 1 It can be seen that the synthesized sample Ge is composed of crystalline and amorphous states;
[0044] The morphology and element mapping distribution of the porous crystalline-amorphous Ge coexisting composite anode material and its crystal / amorphous structure are shown in Figure 2 ,Depend on Figure 2It can be seen from the EDS morphology analysis that Ge element information was detected in the sample, and the selected area electron diffraction SAED showed the characteristics of diffuse amorphous diffraction rings accompanied by crystalline diffraction rings, which is consistent with the crystal structure information obtained by XRD.
[0045] Example 2: A method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, the specific steps are as follows:
[0046] (1) 1 g of germanium dioxide is ultrasonically dispersed in 70 mL of deionized water to obtain a suspension A, and 0.4 mL of 20 wt.% ammonia water is added dropwise under stirring to completely dissolve the powder in the suspension A into a transparent and clear solution B; the germanium in the solution B exists in the form of NH4H(HGeO3)2;
[0047] (2) at a temperature of 30° C., 1.5 mL of a 5% hydroxyethylenediamine solution was dropwise added into 50 mL of deionized water, and then 0.05 g of lithium difluorooxalate borate powder was added to obtain a solution C, and solution B was slowly added to solution C to obtain a mixed solution D;
[0048] (3) The mixed solution D was placed at a temperature of 180° C. for 24 h, cooled to room temperature, and separated into solid and liquid. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain the reaction product E (amorphous GeO2 / C);
[0049] (4) The reaction product E is placed in an air atmosphere, annealed at 400°C for 4 hours, cooled naturally to room temperature, and then placed in a reducing gas (H2-Ar mixed gas) for reduction sintering at 650°C for 2 hours, and cooled to room temperature in the furnace to obtain a pretreated powder F (amorphous / crystalline Ge); the volume fraction of H2 in the H2-Ar mixed gas is 10%;
[0050] (5) 0.7 g of pretreated powder F was ultrasonically dispersed into 100 mL of a mixed solution to obtain a solution G, and the solution G was transferred to a high-temperature and high-pressure hydrothermal reactor, reacted at a temperature of 180° C. for 20 h, cooled to room temperature, and separated from the solid and liquid. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain a precursor powder (porous Ge); the mixed solution was a mixed solution of ethylene glycol, deionized water and hydrofluoric acid, the volume ratio of ethylene glycol to deionized water was 1:1, and the mass concentration of hydrofluoric acid in the mixed solution was 0.1%;
[0051] (6) The precursor powder is placed under protective gas (Ar), sintered at 600°C for 3h, and then cooled to room temperature to obtain a porous crystalline-amorphous Ge coexisting composite anode material;
[0052] The X-ray diffraction (XRD) spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is shown in Figure 3 ,Depend on Figure 3 It can be seen that the synthesized sample Ge is composed of crystalline and amorphous states;
[0053] The scanning electron microscope spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is shown in Figure 4 ,Depend on Figure 4 It can be seen that the synthesized porous crystalline-amorphous Ge has a porous structure with a pore size of about 400nm-1μm;
[0054] The porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is used as the negative electrode of the lithium ion half-cell. The mixture is ground according to the mass ratio of Ge: acetylene black: PVDF = 8:1:1 and then evenly coated on the copper foil as the negative electrode of the battery. The metal lithium sheet is used as the reference electrode and the counter electrode. The electrolyte is 1 mol / L LiPF6 (EC: DMC: EMC = 1:1:1 v / v), and FEC with a volume fraction of 10% is added as a film-forming additive. The cycle performance of the lithium ion half-cell after 200 constant current charge and discharge cycles (current 200 mA / g) is shown in FIG. Figure 5 ,Depend on Figure 5 It can be seen that the lithium-ion half-cell still retains a reversible specific capacity of 1198 mAh / g after 200 cycles of charge and discharge, showing excellent cycle stability and surprisingly high specific capacity.
[0055] Example 3: A method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, the specific steps are as follows:
[0056] (1) 1 g of germanium dioxide is ultrasonically dispersed in 50 mL of deionized water to obtain a suspension A, and 0.2 mL of 20 wt.% ammonia water is added dropwise under stirring to completely dissolve the powder in the suspension A into a transparent and clear solution B; the germanium in the solution B exists in the form of NH4H(HGeO3)2;
[0057] (2) at a temperature of 50° C., 2 mL of a 10% hydroxyethylenediamine solution was dropwise added into 50 mL of deionized water, and then 0.1 g of lithium difluorooxalate borate powder was added to obtain a solution C, and solution B was slowly added to solution C to obtain a mixed solution D;
[0058] (3) The mixed solution D was placed at a temperature of 210° C. for reaction for 36 h, cooled to room temperature, and the solid and liquid were separated. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain the reaction product E (amorphous GeO2 / C);
[0059] (4) The reaction product E was placed in an air atmosphere, annealed at 500°C for 5 h, cooled naturally to room temperature, and then placed in a reducing gas (H2-Ar mixed gas) for reduction sintering at 700°C for 3 h, and cooled to room temperature in the furnace to obtain a pretreated powder F (amorphous / crystalline Ge); the H2 volume fraction in the H2-Ar mixed gas was 15%;
[0060] (5) 0.5 g of pretreated powder F was ultrasonically dispersed into 100 mL of a mixed solution to obtain a solution G, and the solution G was transferred to a high-temperature and high-pressure hydrothermal reactor, reacted at a temperature of 200° C. for 30 h, cooled to room temperature, and separated from the solid and liquid. The solid was washed with deionized water and anhydrous ethanol in turn, and dried to obtain a precursor powder (porous Ge); the mixed solution was a mixed solution of ethylene glycol, deionized water and hydrofluoric acid, the volume ratio of ethylene glycol to deionized water was 1:1, and the mass concentration of hydrofluoric acid in the mixed solution was 0.2%;
[0061] (6) The precursor powder is placed under protective gas (Ar), sintered at 700°C for 4 hours, and then cooled to room temperature to obtain a porous crystalline-amorphous Ge coexisting composite anode material;
[0062] The X-ray diffraction (XRD) spectrum of the porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is shown in Figure 6 ,Depend on Figure 6 It can be seen that the synthesized sample Ge is composed of crystalline and amorphous states;
[0063] The porous crystalline-amorphous Ge coexisting composite anode material of this embodiment is used as the negative electrode of the lithium ion half-cell. The mixture is ground according to the mass ratio of Ge: acetylene black: PVDF = 8:1:1 and then evenly coated on the copper foil as the negative electrode of the battery. The metal lithium sheet is used as the reference electrode and the counter electrode. The electrolyte is 1 mol / L LiPF6 (EC: DMC: EMC = 1:1:1 v / v), and FEC with a volume fraction of 10% is added as a film-forming additive. The cycle performance of the lithium ion half-cell after 200 constant current charge and discharge cycles (current 200 mA / g) is shown in FIG. Figure 7 ,Depend on Figure 7 It can be seen that the lithium-ion half-cell still retains a reversible specific capacity of 1037 mAh / g after 200 cycles of charge and discharge, showing excellent cycle stability and surprisingly high specific capacity.
[0064] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a porous crystalline-amorphous Ge coexisting composite anode material, characterized in that: The specific steps are as follows: (1) dispersing germanium dioxide in deionized water by ultrasonic means to obtain a suspension A, and adding ammonia water dropwise under stirring to completely dissolve the powder in the suspension A into a transparent and clear solution B; (2) at a temperature of 25 to 50° C., dropwise add the hydroxyethylenediamine solution into deionized water, then add lithium difluorooxalate borate powder to obtain solution C, and slowly add solution B into solution C to obtain a mixed solution D; (3) The mixed solution D is placed at a temperature of 160 to 210° C. to react for 12 to 36 hours, cooled to room temperature, and separated into a solid and a liquid. The solid is washed with deionized water and anhydrous ethanol in sequence, and dried to obtain a reaction product E; (4) The reaction product E is placed in an air atmosphere for low temperature annealing for 3 to 5 hours, cooled naturally to room temperature, and then placed in a reducing gas for reduction sintering, and cooled to room temperature in the furnace to obtain a pretreated powder F; (5) ultrasonically dispersing the pretreated powder F into the mixed liquid to obtain a solution G, transferring the solution G to a high temperature and high pressure hydrothermal reactor, reacting at a temperature of 150 to 200° C. for 10 to 30 hours, cooling to room temperature, separating the solid from the liquid, washing the solid with deionized water and anhydrous ethanol in turn, and drying to obtain a precursor powder; the mixed liquid is a mixture of ethylene glycol, deionized water and hydrofluoric acid; (6) The precursor powder is sintered under a protective gas and then cooled to room temperature in the furnace to obtain a porous crystalline-amorphous Ge coexisting composite anode material.
2. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: In step (1), the mass concentration of germanium dioxide in the suspension A is 5-15%, and the mass concentration of ammonia water is 1-3%.
3. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 2, characterized in that: The mass concentration of the hydroxyethylenediamine solution in solution C of step (2) is 1-10%, and the mass concentration of lithium difluorooxalatoborate is 0.2-2%.
4. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: The volume ratio of solution B to solution C in step (2) is 3 to 10:
1.
5. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: In step (4), the low-temperature annealing temperature is 350-500° C.; the reduction sintering temperature is 500-700° C., and the time is 0.2-3 h.
6. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: The reducing gas in step (4) is a hydrogen-argon mixed gas or a hydrogen-nitrogen mixed gas, and the volume content of hydrogen in the reducing gas is 5-15%.
7. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: The volume ratio of ethylene glycol to deionized water in the mixed solution of step (5) is 1:1, and the mass concentration of hydrofluoric acid is 0.05-0.2%.
8. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: The mass concentration of the pretreated powder F in the solution G in step (5) is 0.5-2.0%.
9. The method for preparing the porous crystalline-amorphous Ge coexisting composite anode material according to claim 1, characterized in that: In step (6), the protective gas is argon or nitrogen, the sintering temperature is 400-700° C., and the sintering time is 1-4 hours.
Citation Information
Patent Citations
Preparation method, product and application of Ge-GeO2-TiO2-C nano composite material
CN111653748A
Preparation method of carbon-coated amorphous micron GeOx spherical particle composite anode material
CN115224261A
POROUS AMORPHOUS GeOx AND ITS APPLICATION AS AN ANODE MATERIAL IN LI-ION BATTERIES
US20150171426A1
Porous cellulosic substrates for lithium ion battery electrodes
US20180205114A1
Lithium battery positive electrode material precursor and its preparation method and application
US20240239689A1